L’Intérêt et les limites de la recherche sur l’art de la miniature au Canada. La collection de Bibliothèque et Archives Canada - Vallée, Anne-Elisabeth (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2005)
While rediscovering Library and Archives Canada’s collection of Canadian miniature portraits, this article wishes to shed light on the difficulties of research on miniature painting in Canada. The practice of miniature painting appeared in Canada shortly after the British Conquest of 1763, and became one of the most accessible ways to obtain a “likeness” before the invention of photography about a century later. An examination of LAC’s collection shows the problems that originate from the loss of important information about the miniatures, such as the identity of the model and the artist, the production date and site. This loss of information is partly due to the itinerant way of life of many professional miniaturists, whose identity was lost over the years. To be able to stay in a city for a longer period, professional miniaturists offered their customers a diversified array of services, therefore producing fewer miniatures. As shown by some of the works in LAC’s collection, a high quality miniature is not necessarily the work of a professional miniaturist, but may be the work of an amateur. Despite the loss of essential information, art historians manage to date the works within their approximate period by analysing different components such as the scale, the medium, and the subject’s clothing. In fact, the development of miniature painting in Canada follows roughly the same stages as in France, England, and the United States. From the early very small-scale oval portraits painted in watercolour on ivory, miniature portraits evolved to resemble large-scale portraits and photographs. During the revival of the miniature portrait at the end of the nineteenth century, miniaturists returned to the specificities of the art, by, for example, working on a small scale and using jewel-like frames. Another interesting avenue of research on miniature portraits lies in the different roles played by the miniature in the private or social life of the owners. Always an object of memory, the miniature may be worn as an ornament, or, because of its high symbolic value, may become a fetish.